1985
DOI: 10.1111/j.1752-7325.1985.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

A Symposium on the New Fight for Fluorides: Part II: Priorities to Preserve Fluoride Uses: Rationales and Strategies

Abstract: Well-planned, new initiatives are required to preserve fluoride uses, especially water fluoridation. Discussed are barriers to fluoride promotion, evidence about public and health-care providers' knowledge and opinions about fluoride use and decision making, implications of sources of public information on fluorides, consequences to professionals and the public of being misinformed about fluorides, and four general strategies for promoting fluorides under varying conditions. Educational and political initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…14 Because people’s source of information is related to their level of support of or opposition to water fluoridation, 14,30 provision of water fluoridation materials in dental offices may be effective because dentists are seen as credible and accurate sources of information. 31 However, Isman 32 found that people who cited a dentist as their primary source of water fluoridation information were not significantly more likely to vote for fluoridation, understand its purpose or be influenced by arguments for or against fluoridation. In addition, their rating of preventive dental care did not differ significantly from that of people who cited the media or other sources of information regarding water fluoridation.…”
Section: Dentists’ Effectiveness In Promoting Water Fluoridationmentioning
confidence: 99%
“…14 Because people’s source of information is related to their level of support of or opposition to water fluoridation, 14,30 provision of water fluoridation materials in dental offices may be effective because dentists are seen as credible and accurate sources of information. 31 However, Isman 32 found that people who cited a dentist as their primary source of water fluoridation information were not significantly more likely to vote for fluoridation, understand its purpose or be influenced by arguments for or against fluoridation. In addition, their rating of preventive dental care did not differ significantly from that of people who cited the media or other sources of information regarding water fluoridation.…”
Section: Dentists’ Effectiveness In Promoting Water Fluoridationmentioning
confidence: 99%